2010
DOI: 10.1109/tec.2010.2042220
|View full text |Cite
|
Sign up to set email alerts
|

Online Sensorless Induction Motor Temperature Monitoring

Abstract: A sensorless internal temperature monitoring method for induction motors is proposed in this paper. This method can be embedded in standard motor drives, and is based on the stator windings resistance variation with temperature. A small ac signal is injected to the motor, superimposed to the power supply current, in order to measure the stator resistance online. The proposed method has the advantage of requiring a very low-level monitoring signal, hence the motor torque perturbations and additional power losse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The integration of the KF layer into the Contiki system stack is shown in Fig. 12. 6LoWPAN is defined encapsulation and header compression mechanisms that allow IPv6 packets to be sent to and received from IEEE802.15.4 links, whose full name is IPv6 over Low power Wireless Personal Area Networks (Shelby and Bormann, 2010). It is an adaptation layer of the Ipv6 protocol for WSN.…”
Section: The Prediction Stage Of the Kalman Filtermentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of the KF layer into the Contiki system stack is shown in Fig. 12. 6LoWPAN is defined encapsulation and header compression mechanisms that allow IPv6 packets to be sent to and received from IEEE802.15.4 links, whose full name is IPv6 over Low power Wireless Personal Area Networks (Shelby and Bormann, 2010). It is an adaptation layer of the Ipv6 protocol for WSN.…”
Section: The Prediction Stage Of the Kalman Filtermentioning
confidence: 99%
“…The thermal behavior of an induction machine largely determines the maximum lifetime, to cope with overload conditions and also the accuracy in a high-performance controller (Sonnaillon et al, 2010). Normally, three methods are used for the temperature monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Alternate QD Model (AQDM) included leakage saturation, magnetizing saturation, and distributed system effects in the rotor circuits which CQDM in [8][9][10][11][12][13] respectively. The steady-state equivalent circuit representing the AQDM in [14] is shown in Fig.…”
Section: Alternate Qd Induction Machine (Aqdm)mentioning
confidence: 99%
“…Among many efforts to obtain optimal performance, an Adaptive Maximum Torque Per Amp (Adaptive MTPA) control of induction motor drives was proposed [7]. One interesting approach to develop an Adaptive MTPA control is to employ an alternate qd induction machine model (AQDM) rather than the classical qd model (CQDM), such as in [8][9][10][11]. The Adaptive MTPA control strategy set forth in [7] has demonstrated the ability to achieve the commanded torque with good accuracy, regardless of temperature variation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the consideration of rotor resistance variation has been a significant issue in control design, particularly in the case of optimal controls [2,[5][6][7][8][9][10]. Herein, it is shown that the MTPA control strategy in [2] performs sub-optimally as the stator surface temperature (and presumably rotor temperature) varies.…”
Section: Introductionmentioning
confidence: 99%